(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Although there has been a significant interest in corporate social responsibility (CSR) in recent years, there is lack of adequate studies regarding the status of CSR practices in Nepal. The existing studies generally suffer from the narrow conceptualization of CSR, focus on selected companies or industry sector only and from the relatively small sample size. Objectives: This paper aims to identify the status of CSR practices in the Nepalese context. Methods: This study uses questionnaire survey method by taking a sample of 168 listed companies of Nepal representing diverse industry sectors. Descriptive statistics, one-way ANNOVA and t-test have been used to analyze the collected data. Results: The overall status of CSR practices in Nepal is above the moderate level. The most common CSR practices in Nepal relate to corporate governance as well as customers whereas the least common CSR practices include environment and community related activities. Likewise, level of CSR practices is significantly higher among large firms compared to small and medium sized enterprises (SMEs). However, there is no significant difference on the status of CSR practices between banking sector and non-banking sector firms. Conclusions: While the overall status of CSR practices in Nepal is above the moderate level, Nepalese companies are not paying adequate attention on community and environment related issues. The results also indicate that size of the firm tend to affect the level of CSR practices in the Nepalese context though the difference on CSR practices between small and medium sized firms is not statistically significant. Implications: The government and policy makers may consider giving tax exemption or any other clearly spelled out incentives particularly to the environment and community related CSR activities. Likewise, managers and other stakeholders including the government may focus on identifying and overcoming the barriers for CSR practices among SMEs in Nepal.